The Effect of CD4+CD28 T Cells and Their Pathological Role in Pregnant Women with Diabetes with Role C. Peptide in Diabetes Diagnosis - AlAbrihemy, Zahraa Abbas A.; Ali, Haider H. Mohammed; Saadi, Kawkab A. Al (Jour Med Resh and Health Sci, 2023)
Background: Autoimmune diseases are a diverse group of conditions characterized by abnormal B cell reactivity. It is associated with T-cell responses. CD4, also known as Th, is a type of white blood cell. Helper T cells play a crucial role in maintaining immune cell homeostasis and protecting the host from pathogens (GDM), a complication of immune dysfunction in pregnant women that affects approximately 5-10% of all pregnancies CD28, a 44-kDa membrane glycoprotein, In almost all human T lymphocytes at birth. A small peptide that links the two chains of the proinsulin molecule, and is separated before insulin is released. It is released in equal amounts with insulin by pancreatic beta cells. Objective: To estimate the percentage of T-cell, evaluate the percentage of C-peptide in DM. Methods: Methods: 58 pregnant women with diabetes participated in the study, including 24 pregnant women with T1DM and 34 pregnant women with T2DM. C-peptide levels. Results: All pathological samples showed a decrease in CD4+ Tcell concentration compared to control. Samples taken from T1DM patients also showed a decrease in the presence of other diseases and bacterial infections compared to T2DM patients and the absence of bacterial infections. They also showed an increase in C-peptide in diabetic patients in the presence of other diseases. C-peptide CD28 did not appear and there were no statistically significant differences. Conclusion: There was a positive correlation between CD4 + T-cell, CD28 immunoreactivity to the incidence of T1DM, T2DM, and C-peptide in DGM.